The degree of left atrial structural remodeling impacts left ventricular ejection fraction in patients with atrial fibrillation - Mehmet Akkaya; Nassir Marrouche; Koji Higuchi; Matthias Koopmann; Kavitha Damal; Eugene Kholmovski; Chris Mcgann (KARE Publishing, 2014)
The extent of left atrial (LA) wall structural remodeling (fibrosis) detected by late gadolinium enhancementmagnetic resonance imaging (LGE-MRI) is correlated with advanced atrial fibrillation (AF). The concomitant occurrence of AF and left ventricular (LV) dysfunction is not uncommon. We studied the effect of LA fibrosis, a confounder of both AF and LV dysfunction, on LV ejection fraction (EF). For the analysis, we identified and included 384 patients from our retrospective AF database who underwent LGE-MRI and transthoracic echocardiography prior to AF ablation. Based on the degree of LA fibrosis, patients were categorized into four stages as: Utah 1 (<5% LA fibrosis), Utah 2 (5-20% fibrosis), Utah 3 (20-35% fibrosis), and Utah 4 (>35% fibrosis). The average pre-ablation LVEF was 60.5%+-8.5% (n=24) in Utah stage 1 patients, 55.7%+-10.3% (n=240) in Utah stage 2 patients, 51.7+-11.5% (n=90) in Utah stage 3 patients, and 48.9%+-11.6% (n=30) in Utah stage 4 patients (p<0.001, one-way ANOVA). The percentage of LA fibrosis was significantly negatively correlated to LVEF pre-ablation in a univariate analysis (p<0.001). In a multivariate model accounting for age, gender, AF type, and comorbidities such as diabetes and hypertension, Utah stage remained a significant predictor of pre-ablation EF (p<0.001). Patients with extensive LA fibrosis appear to have depressed LV function pre-ablation, suggesting that structural remodeling in the LA may also be triggering and promoting remodeling within the ventricular myocardium.